Human-tapir conflict: a case report of a lowland tapir attack and a global review of such encounters - Araujo Goebel, Larissa Gabriela; Alvares Oliveira, Marcela; Rodrigues Longo, Gabriela; Bueno Landis, Mariana; Medici, Emília Patrícia (Ethnobiology and Conservation, 2025)
Anthropogenic alterations to ecosystems have resulted in proximity between humans and animals, imposing coexistence challenges. Here, we present a report of a tapir attack on a human in the Brazilian Amazon. In addition, we conducted a global literature review covering tapir-related incidents, compiling data from various parts of the world. Data was collected from testimonies from those involved in the incident aforementioned, without inducing the subjects. The global literature review was carried out by searching Google Scholar, digital communication sites, and YouTube for papers reporting attacks by tapirs on humans. In addition to the report described in this article, we found four reports of tapir attacks on humans around the world. In all of them, there were lacerations on the hands, which were possibly used by the humans as a defense. There was only one recorded death as a result of a tapir attack. Our study discusses potential explanations for the attacks since tapirs tend to express furtive behavior in risky situations. This study seeks to deepen the knowledge of the dynamics of human-tapir coexistence to improve conservation efforts and strategies aimed at the well-being of ecosystems. Keywords: Coexistence – Human-fauna interaction – Ungulate